2019
DOI: 10.1111/acer.14110
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐Induced Interleukin‐17 Expression Causes Murine Lung Fibroblast‐to‐Myofibroblast Transdifferentiation via Thy‐1 Down‐Regulation

Abstract: Background: Alcohol exposure induces TGFb1 and renders the lung susceptible to injury and disrepair. We determined that TGFb1 regulates myofibroblast differentiation through the loss of Thy-1 expression and consequent induction of a-SMA. TGFb1 is important for T helper 17 (Th17) differentiation and IL-17 secretion, which in turn participates in tissue repair. We hypothesized that alcohol induces Th17 differentiation via TGFb1 and that IL-17 produced by these cells contributes to the development of profibrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…Therefore, infiltrated neutrophils and/or lymphocytes might be responsible for increased IL-17 levels in BALF. Recent study demonstrated using 8 weeks alcohol drinking model in mice that alcohol-induced IL-17 and Th17 immune response promotes lung fibroblast differentiation to myofibroblasts ( Neveu et al, 2019 ), eventually this could cause fibroproliferative microenvironment in lungs of chronic alcohol drinkers. Therefore, IL-17 might be an important mediator in alcohol-induced lung injury and subsequent fibroproliferative disorders, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, infiltrated neutrophils and/or lymphocytes might be responsible for increased IL-17 levels in BALF. Recent study demonstrated using 8 weeks alcohol drinking model in mice that alcohol-induced IL-17 and Th17 immune response promotes lung fibroblast differentiation to myofibroblasts ( Neveu et al, 2019 ), eventually this could cause fibroproliferative microenvironment in lungs of chronic alcohol drinkers. Therefore, IL-17 might be an important mediator in alcohol-induced lung injury and subsequent fibroproliferative disorders, which warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Tal fato pode ser observado pelo aumento da concentração de marcadores de fibrose pulmonar como Timp 1, cadeias de colágeno tipo 1 (Col1a1), e α-SMA. (35,36) Outrossim, emerge uma clara evidência do papel crucial do sistema imunológico na perpetuação e agravamento do estado inflamatório, que eventualmente culmina na fibrose tecidual. A investigação dos marcadores da linhagem hematopoiética das células linfoides inatas do tipo 2 (ILC2) revela um incremento notável de KLRG1+ sob a influência do álcool, indicando uma intensificação da produção e ativação dessas células.…”
Section: Sistema Endocrinounclassified
“…Thy-1 is silenced within FF by epigenetic mechanisms, such as DNA methylation ( Sanders, Pardo et al, 2008 ). Epigenetic silencing of Thy-1 leading to pathogenic alteration in fibroblasts, is driven by aging and TGF-β ( Neveu, Mills et al, 2015 ), TLR4 ( Xing, Nie et al, 2015 ), IL-17 ( Neveu, Staitieh et al, 2019 ) and hypoxia ( Robinson, Neary et al, 2012 ). A recent study described a regulatory axis of Thy-1 expression involving the transcription factor YY1 and miR-214 in the context of lung fibrosis ( Chen, Yang et al, 2020 ).…”
Section: Thy-1–integrin Interaction In Pathophysiologymentioning
confidence: 99%